2012
DOI: 10.1002/app.37512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial delignification of kenaf bast fibers for radiation graft copolymerization

Abstract: Malaysian kenaf bast fiber was treated by acidic chlorite to be applied for a trunk polymer radiation-induced graft copolymerization. The delignification conditions such as temperature, reaction time, and sodium chlorite (NaClO 2 ) loading were optimized from the viewpoints of density, tensile strength, and reactivity of grafting. It was found that delignification condition at 80 C for 6 h with 0.5% NaClO 2 gave 91% of lignin removal from the kenaf bast fibers. In this case, the density, fineness, and tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…10). Mohamed et al have also confirmed these results when they attempted to graft 4-chloromethyl styrene onto delignified kenaf fibres (Mohamed et al, 2013). However, Ali Ayoub et al have shown that lignin can be grafted by styrene monomer at low doses (Ayoub et al, 2014).…”
Section: Direct Irradiation Of Natural Fibre Reinforced Compositesmentioning
confidence: 86%
See 1 more Smart Citation
“…10). Mohamed et al have also confirmed these results when they attempted to graft 4-chloromethyl styrene onto delignified kenaf fibres (Mohamed et al, 2013). However, Ali Ayoub et al have shown that lignin can be grafted by styrene monomer at low doses (Ayoub et al, 2014).…”
Section: Direct Irradiation Of Natural Fibre Reinforced Compositesmentioning
confidence: 86%
“…Khan and Khan reported that γ-irradiated jute fibres are better dispersed into PP (macro) molecule to be grafted is then added. The grafting occurs thanks to the radicals already formed on the fibre during irradiation (Mohamed et al, 2013;Sharif et al, 2013); (ii) the second pathway is known as the mutual grafting and can be used for "grafting-from" method: the fibre is impregnated with the molecule and then irradiated, leading to the grafting of the molecule on the fibre and its possible free radical polymerization (Kaur et al, 2010;Kodama et al, 2014;Sonnier et al, 2015). Desmet et al (Desmet et al, 2011) consider that mutual grafting is less detrimental for cellulose because solvent and monomer can act as stabilizers during irradiation.…”
Section: Direct Irradiation Of Natural Fibre Reinforced Compositesmentioning
confidence: 99%
“…Fiber micrographs were obtained using a scanning electron microscope (FE I Quanta 200). The fibers w ere o bserved u sing a vertical sample holder under high vacuum at a voltage of 12.5 kV and a working contradiction with literature, and especially works of Sharif et al [29] and Mohamed et al [30]. Nevertheless, these authors carried out preirradiation method while the mutual radiation grafting was chosen in the present work.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 97%
“…Mohamed et al [30] also studied the inhibitory effect of lignin with kenaf fibers. The kenaf fibers were delignified with sodium chlorite solution NaClO 2 before radiation grafting.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the materials processing methods with the aid of physical effects, chemical effects and biology effects between high-energy radiation (such as gamma ray and electron beam) and matter is called radiation processing. At present, although the radiation processing obtain the very good application in many fields of polymwric materials [1][2][3][4][5][6][7][8][9][10][11][12][13], while the parathion of polymer-based nanocomposites via radiation technology is still a new field of polymer radiation processing.…”
Section: Introductionmentioning
confidence: 99%